What kind of matching groups makes students benefit more? The role of reviewer expertise and document quality within-groups - Zheng Zong; Christian D. Schunn (Acta Psychologica)
Peer feedback has proven to be practically helpful for students in achieving learning outcomes, especially through peer feedback among students in matching achievement groups. However, some researchers have raised concerns about whether students would be better served by being matched with different achievement groups rather than ‘random’ or same-level matching methods. No studies have investigated whether other ways of matching groups would change outcomes. The study examined the impact of reviewers' expertise and document quality changes on learning outcomes in the matching group through a large dataset involving three large biology courses. Results reveal that matching groups with high reviewer competence are associated with higher learning outcomes for students with low performance. Although receiving more feedback is often negatively associated with learning, receiving more feedback from those with high reviewer expertise is positively related to learning. The study further suggests that educators can focus on the overall competence of members in the assigned reviewers instead of finding matching individuals. In addition, educators and researchers should consider the roles of both providing and receiving feedback based on the ability of matching groups. Future research could use questionnaires or experimental methods to examine student motivation and further determine the causal relationship between the relative benefits/risks of different matching groups on learning outcomes.